Meningkatkan prestasi belajar matematika materi penjumlahan dan pengurangan pecahan menggunakan media teropong pecahan pada siswa sekolah dasar - Wahidatul Arifah (Universitas Sebelas Maret, 2022)
This research aims to improve the learning achievement addition and subtraction of fractions using props binoculars fractions in fourth grade students of SDN Gumelem I. This type of research is a classroom action research. The subjects were fourth grade students SDN Gumelem 1 totaling 14 students. Collecting data technique used the observation and test method with instrument research sheets of observation and test questios. Data were analyzed by descriptive quantitative and qualitative. The result of this research in pre-action shows that there was only 4 students that reach the KKM or 26,67%. The amount of students that reach the KKM increased in the first cycle reaching 8 students or 53,33% and increase again in cycle two that reaching 13 students or 86,67%.